Ginseng Conduces Degeneration of Differentiating Tissues in Developing Albino Mice (Medical Forum Monthly, 2024)
Objective: The current study was conducted to evaluate its effects on developing skin, heart and intestines, derivatives of ectoderm, mesoderm and endoderm respectively, when given during pregnancy to albino mice.Study Design: Experimental Randomized controlled trial study.Place and Duration of Study: This study was conducted at Anatomy Department, University of Health Sciences, Lahore from Jan 2011 to July 2011.Materials and Methods: Twelve pregnant albino mice were divided into two groups of 6 each; group A was given distill water, Human therapeutic dose (HTD) (780mg/kg/day) was dissolved in 0.1ml of distilled water and was administered to the animals of group B for entire length of pregnancy. Fetuses were delivered and dissected on 18th day of gestation. Tissue samples comprising, skin, heart and small intestine derivatives of ectoderm, mesoderm and endoderm respectively, were removed and processed for light microscopic study.Results: In the current study, the difference between dead and alive fetuses, when compared between groups was found to be statistically significant (p value < 0.05). In addition, the histological examination of the above tissues revealed extensive cell death resulting into loss of normal architecture of skin, heart and small intestine. Cells showed pyknotic nuclei and scanty cytoplasm, indicating process of apoptosis, which when compared between groups was found to be statistically significant (p<0.05).Conclusion: It is suggested, therefore, that further investigations and monitoring of additional tissues for the effects of Ginsenosides during pregnancy are warranted.